2019
DOI: 10.30520/tjsosci.524826
|View full text |Cite
|
Sign up to set email alerts
|

Dünya Deni̇z Ti̇careti̇ Ve Türki̇ye Diş Ti̇careti̇ İli̇şki̇leri̇: Ekonometri̇k Bi̇r Anali̇z

Abstract: Deniz, denizcilik, deniz taşımacılığı vb. kavramlar dünya tarihi boyunca önemini yitirmemiş, medeniyetlerin oluşmasında ve gelişmesinde önemli roller üstlenmiştir. Dünya mal ticaretinin yaklaşık %75'i deniz yolu ile yapılmaktadır. Deniz taşımacılığının hala en çok tercih edilen taşımacılık alternatifi olmasının birçok nedeni bulunmaktadır. Türkiye de toplam ihracat ve ithalatının yarısından fazlasının deniz yolu ile yapıldığı önemli bir deniz ülkesidir. Çalışmada, dünya deniz ticareti ve Türkiye dış ticaret il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Among others in field literature, this paper has similarities and differences with Graham, Peltomäki, and Piljak (2016), Ruan, et al (2016), Yıldız and Bucak (2017), Cihangir (2018), Eryuzlu (2019), Kiracı and Akan (2020), Gao, Zhao, and Zhang (2021), Bandyopadhyay and Raji (2021)'s paper in terms of obtained results.…”
supporting
confidence: 66%
See 2 more Smart Citations
“…Among others in field literature, this paper has similarities and differences with Graham, Peltomäki, and Piljak (2016), Ruan, et al (2016), Yıldız and Bucak (2017), Cihangir (2018), Eryuzlu (2019), Kiracı and Akan (2020), Gao, Zhao, and Zhang (2021), Bandyopadhyay and Raji (2021)'s paper in terms of obtained results.…”
supporting
confidence: 66%
“…The authors concluded a long-run association between the BDI and Istanbul Freight index (Zeren and Kahramaner, 2019). Eryuzlu (2019) pointed out the relationship between the BDI and Turkey's total exports and imports. The research sample was tested through the Toda-Yamamoto test and Hatemi-J asymmetric causality test.…”
Section: Literature Overviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The BDI variable represents the price of the global maritime transport (Geman, 2008, p. 181), which is a cost indicator for shippers and a revenue indicator for transporters. With this feature, it stands out as a factor affecting the foreign trade of countries (Eryüzlü, 2019) and has a structure covering all other sub-indices (Zeren and Kahramer, 2019). Finally, the RINT variable is the real interest rate obtained by subtracting the inflation rate from the nominal interest rate in the United States.…”
Section: Resultsmentioning
confidence: 99%